Wettability Alteration of Sandstone by Chemical Treatments - Yan-ling Wang; Li Ma; Bao-jun Bai; Guan-cheng Jiang; Jia-feng Jin; Zeng-bao Wang (Journal of Chemistry)
Liquid condensation in the reservoir near a wellbore may kill gas production in gas-condensate reservoirs when pressure drops lower than the dew point. It is clear from investigations reported in the literature that gas production could be improved by altering the rock wettability from liquid-wetness to gas-wetness. In this paper, three different fluorosurfactants FG1105, FC911, and FG40 were evaluated for altering the wettability of sandstone rocks from liquid-wetting to gas-wetting using contact angle measurement. The results showed that FG40 provided the best wettability alteration effect with a concentration of 0.3% and FC911 at the concentration of 0.3%.